2021
DOI: 10.2478/raon-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of soft-tissue sarcoma on MRI correlates with grade of malignancy

Abstract: Background The aim of the study was to assess whether the configuration of primary soft-tissue sarcoma (STS) on MRI correlates with the grade of malignancy. Patients and methods 71 patients with histologically proven STS were included. Primary STS were examined for configuration, borders, and volume on MRI. The tumors were divided into high-grade (G3), intermediate-grade (G2) and low-grade (G1) STS according to the grading sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…The configuration of STS has been reported several times in recent years. Higher grade (G2/3) STS display a polycyclic/ multilobulated structure, and this configuration may help predict tumor recurrence (26,27). In the present study, the multilobulated structure was associated with high HIF-1α expression and might be a potential predictor of poor patient prognosis.…”
Section: Discussionsupporting
confidence: 51%
“…The configuration of STS has been reported several times in recent years. Higher grade (G2/3) STS display a polycyclic/ multilobulated structure, and this configuration may help predict tumor recurrence (26,27). In the present study, the multilobulated structure was associated with high HIF-1α expression and might be a potential predictor of poor patient prognosis.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, radiographic size is not always a reliable radiomic feature for diagnosis. Although ovoid/nodular configurations cannot distinguish the grade of malignancy (i.e., high-, intermediate, and low-grade soft tissue tumors) on MRI [ 43 ], it may differentiate IM lipomas from ALTs/WDLSs. Based on our results, ALTs/WDLSs had a more compact (sphere-like) shape than IM lipomas, as evidenced by the surface area-to-volume ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, ALTs/WDLSs had a more compact (sphere-like) shape than IM lipomas, as evidenced by the surface area-to-volume ratio. This radiomic feature may be correlated to ovoid/nodular configurations on MRI [ 43 , 44 ]. We can observe that this shape difference may also reflect excessive cell proliferation and/or non-lipomatous or nodular fibrous septa, which showed a fluffier consistency in ALTs/WDLSs [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sedaghat et al reported that the MRI configuration of soft-tissue sarcoma (STS) correlates with the grade of malignancy. 9 Higher-grade STS are multilobulated, whereas low-grade STS are ovoid or streaky. Infiltrative lesions suggest a higher grade.…”
Section: Limitations Of the Ultrasoundmentioning
confidence: 99%
“…Infiltrative lesions suggest a higher grade. 9 Additionally, MRI is a valuable tool for postsurgical follow-up of various soft tissue tumors [10][11][12][13] such as recurrent dermatofibrosarcoma protuberans (DFSP) which appear as nodular, homogeneous, and well-defined enhancing lesions. 10 Furthermore, MRI can assess the occurrence of post-treatment changes such as subcutaneous and muscle edema.…”
Section: Limitations Of the Ultrasoundmentioning
confidence: 99%